Perlindungan Hukum atas Tidak Berfungsinya Proses Transaksi melalui Smart Contract pada Sistem Blockchain - Andi Jazmine Alfatiha Yusuf; Pieter E. Latumeten (IAIN Langsa, 2026)
This study aims to analyze the characteristics of smart contracts in e-commerce transactions and examine legal certainty and legal protection when smart contracts fail to operate as intended. The research employs a normative juridical method using statutory, legal principle, and literature approaches. The findings show that smart contracts fulfill the elements of electronic agreements and remain valid under civil law as long as they comply with the principle of consensualism. Legal protection may be provided through preventive measures during the pre-contract stage and repressive mechanisms after disputes arise, considering the legal relationship among buyers, sellers, and smart contract developers. This study contributes to the development of legal discourse by emphasizing the need for regulatory reform to ensure that blockchain-based smart contracts operate in accordance with the principles of legal certainty and legal protection within the Indonesian legal system.